PENGARUH PROGRAM LITERASI DALAM KESEPAKATAN KELAS TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 4 SDN BATUPUTIH - Kuswanto, Jepi; Rahmatullah, Rahmatullah; Anwar, Khairil; Sulfana, Evi Yanti (Universitas Muhammadiyah Mataram, 2024)
Literacy is one of the most important abilities in successful learning. Therefore, research was conducted to determine the effect of implementing a literacy program on the Indonesian language learning outcomes of class IV students at SDN Batuputih, Kec. Plampang. The research method used was pre-Experimental Design with a sample of 16 class IV students. Data was collected using test instruments, then analyzed using descriptive and inferential statistical techniques. This research resulted in an increase in graduation achievement with the average score for Indonesian language lessons going from 25% to 81.25% classically. Apart from that, the level of students' ability and mastery of the material increased after the Literacy Program was implemented where students who reached the original KKM limit were only 50% to 100%. The implementation of the Literacy Program has a significant influence on improving Indonesian language learning outcomes for class IV students at SDN Batuputih, Kec. Plampang.